Advances in mesoporous silica nanoparticles for targeted stimuli-responsive drug delivery. (February 2015) - Baeza, Alejandro; Colilla, Montserrat; Vallet-Regí, María
<x xml:space="preserve">Abstract</x> Introduction: Mesoporous silica nanoparticles (MSNPs) are one of the most promising inorganic drug delivery systems (DDSs). The design and development of tumour-targeted MSNPs with stimuli-responsive drug release capability aim at enhancing the efficiency and minimising the side effects of anti-tumour drugs for cancer therapy. Areas covered: This review provides an overview of the scientific advances in MSNPs for tumour-targeted stimuli-responsive drug delivery. The key factors that govern the passive accumulation of MSNPs within solid tumours such as size, shape and surface functionalisation are roughly described. The different active targeting strategies for the specific retention and uptake of MSNPs by tumour cells are also outlined. The approaches developed so far for the synthesis of smart MSNPs capable of releasing the trapped drugs in response to internal or external stimuli and their applications are reviewed. Critical considerations in the use of MSNPs for the treatment of cancer treatment are discussed. The future prospects and key factors concerning the clinical application of MSNPs are considered throughout the manuscript. Expert opinion: MSNPs are promising nanocarriers to efficiently transport and site-specifically deliver highly toxic drugs, such as chemotherapeutic agents for cancer treatment. However, there are certain issues that should be overcome to improve the suitability of MSNPs for clinical applications. Increasing the penetration capability of MSNPs within tumour tissues, providing them of appropriate colloidal stability in physiological fluids and ensuring that their active targeting capability and stimuli-responsive performance are preserved in complex biological media are of foremost significance. Few in vivo evaluation tests of MSNPs have been reported and much research effort into this field is mandatory to be able to move from bench to bedside.